Potential Intersections between lncRNA, Vascular Cognitive Impairment, and Immunization Strategies: Insights and Future Directions - Yishu Fan; Bo Xiao; Mengqi Zhang (Vaccines, 2024)
Vascular cognitive impairment (VCI) encompasses a wide range of cognitive disorders stemming from cerebrovascular issues, such as strokes or small vessel disease. These conditions often pose challenges to traditional diagnostic approaches due to their multifactorial nature and varied clinical presentations. Recently, next-generation sequencing (NGS) technologies have provided detailed analyses of long non-coding RNAs (lncRNAs) in the molecular pathobiology of VCI. These new findings help with molecular-based diagnostics and treatments of VCI. Within this realm, the concept of immune modulation, especially through specific vaccinations, emerges as a promising therapeutic strategy in VCI mitigation. In this review, we comprehensively elucidate the function of lncRNAs in VCI, emphasizing the advanced understanding of VCI’s molecular underpinnings made possible through NGS technologies. Significant focus is placed on the immune system’s role in VCI, particularly the neuroinflammatory processes which are consequential to cerebrovascular abnormalities. We believe that lncRNAs participate in regulating these immunological pathways, potentially guiding the development of vaccines targeting VCI. In this context, we propose a novel perspective: using knowledge about lncRNA profiles and functions to guide vaccine development, we can potentially exploit the body’s immune response to mitigate or prevent VCI. This approach has the potential to revolutionize VCI management by introducing targeted immunization strategies informed by molecular signatures, a concept that remains largely unexplored in current research endeavors. In addition, we summarize current progress and propose future directions, advocating for robust, interdisciplinary studies to validate the potential intersections between lncRNA landscapes, VCI pathology, and immunology. This review aims to spur innovative research and promote the development of lncRNA-informed vaccine strategies as proactive interventions against the cognitive consequences of VCI.